2003
DOI: 10.1152/jn.01155.2002
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of BK Ca2+-Activated K+Channels to Auditory Neurotransmission in the Guinea Pig Cochlea

Abstract: Large-conductance calcium-activated potassium (BK) channels are known to play a prominent role in the hair cell function of lower vertebrates where these channels determine electrical tuning and regulation of neurotransmitter release. Very little is known, by contrast, about the role of BK channels in the mammalian cochlea. In the current study, we perfused specific toxins in the guinea pig cochlea to characterize the role of BK channels in cochlear neurotransmission. Intracochlear perfusion of charybdotoxin (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
60
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 44 publications
9
60
0
Order By: Relevance
“…Spontaneous firing develops also in injured myelinated afferents after SNL [53], thus our findings that axotomized myelinated -but not adjacent uninjured afferents-develop increased excitability, and axotomized medium-sized fibers lose I K(Ca) , contribute additional support to the argument that injured (and not uninjured) myelinated afferents mediate neuropathic pain behavior after SNL [6]. Because BK channels control neurotransmitter release [86] and inter-neuronal glutaminergic synaptic efficacy [72], it is also likely that loss of BK currents in small and medium sized neurons after axotomy may enhance synaptic transmission of afferent signaling, as well. In addition to loss of I K(Ca) currents in a manner directly related to nerve injury, we have also previously shown that neuropathy decreases I Ca [60,61], a mechanism that may reduce the activation of K (Ca) currents in addition to the direct effect of SNL, thus leading to a higher enhancement of excitability.…”
Section: Discussionsupporting
confidence: 61%
“…Spontaneous firing develops also in injured myelinated afferents after SNL [53], thus our findings that axotomized myelinated -but not adjacent uninjured afferents-develop increased excitability, and axotomized medium-sized fibers lose I K(Ca) , contribute additional support to the argument that injured (and not uninjured) myelinated afferents mediate neuropathic pain behavior after SNL [6]. Because BK channels control neurotransmitter release [86] and inter-neuronal glutaminergic synaptic efficacy [72], it is also likely that loss of BK currents in small and medium sized neurons after axotomy may enhance synaptic transmission of afferent signaling, as well. In addition to loss of I K(Ca) currents in a manner directly related to nerve injury, we have also previously shown that neuropathy decreases I Ca [60,61], a mechanism that may reduce the activation of K (Ca) currents in addition to the direct effect of SNL, thus leading to a higher enhancement of excitability.…”
Section: Discussionsupporting
confidence: 61%
“…BK channels were shown to be present in the stria vascularis by immunocytochemistry (8) and electrophysiology (28) as well as in fibrocytes of the spiral ligament by electrophysiology (29). Although we cannot exclude effects on the endocochlear potential in BK␣ Ϫ/Ϫ mice older than those studied here, we were unable to detect any phenotypical change in the stria vascularis in BK␣ Ϫ/Ϫ mice, in line with the described profile of hearing loss.…”
Section: Bk␣ Deletion Leads To Hearing Loss Despite Normal Phenotypes Ofmentioning
confidence: 52%
“…BK channel mRNA (7,8) and protein expression (8) were shown in IHCs, indicating that I K,f flows through BK channels. The presumed physiological roles of BK channels are (i) a decrease of the membrane time constant even at the resting potential and (ii) fast repolarization of the receptor potential.…”
mentioning
confidence: 99%
“…Indeed, acute blockade of the BK␣ subunit by perfusion of the BK channel blocker iberiotoxin into the guinea pig cochlea reduces the auditory nerve compound action potential (21), suggesting that compensatory mechanisms may be responsible for the normal hearing we observe in mice genetically designed to lack the BK␣ subunit at all developmental stages. Moreover, this compensation could occur in cells of the cochlea other than the IHCs.…”
Section: Regulation Of Other Gene Products Does Not Compensate For Thmentioning
confidence: 98%
“…IHCs express a potassium current (termed I K,f ) pharmacologically similar to BK currents, showing sensitivity to low concentrations of tetraethylammonium, charybdotoxin, and iberiotoxin (17)(18)(19)(20)(21). The transcript for the BK␣ subunit has been detected in IHCs (22,23), and immunostaining has verified expression of the BK␣ subunit in IHCs (17,20,21,24). Additionally, transcripts for both the BK␤1 and ␤4 subunit have been identified in IHCs (22).…”
mentioning
confidence: 99%